Modification of Electrical Supplay System on Fuel Feeder Gas Engine Power Plant Based on Inverter (DC-AC) in PLTMG Balai Pungut - Muhammad Fadlan Syahputra; Siti Anisah; Adi Sastra P Tarigan (Budapest International Research and Critics University, 2022)
The Balai Pungut Gas Engine Power Plant (PLTMG) is one of the plants in the Pekanbaru sector and part of the North Sumatra Plant (KITSBU). This PLTMG has a capacity of 7 x 17 MW with dual fuel systems, namely Solar and Gas. For gas fuel, it is the main fuel of PLTMG because the gas efficiency is higher than diesel. However, diesel fuel is the main fuel that must be used for PLTMG engines as gas fuel, so diesel fuel must be supplied continuously for the consumption of PLTMG needs. Therefore, the Fuel Feeder system for Solar fuel must have reliable performance. However, at PLTMG Balai Pungut, there are often problems or problems with the Fuel Feeder, this is because the protection system shows the occurrence of a Fuel Feeder travel system that occurs in fuel feeder equipment components that experience voltage input instability. After analysis due to the impact of resources in the SUTT System Network as a supply center line experienced Transient. Therefore, the Power Supplay Electrical System for Fuel Feeder equipment needs to be modified with the addition of an inverter, the source of which is taken from the battery as a source of constant direct voltage and voltage converted back and forth to play the electricity system of the Fuel Feeder PLTMG Balai Pungut.